I am all ears: listening exams with AI and its traces on foreign language learners’ mindsets, self-competence, resilience, and listening improvement - Mohamed Sayed Abdellatif; Mohammed A. Alshehri; Hamoud A. Alshehri; Waheed Elsayed Hafez; Mona G. Gafar; Ali Lamouchi (Language Testing in Asia)
Abstract With the growing prevalence of artificial intelligence (AI) in educational settings, this research aimed to understand how AI-based assessments affect EFL learners beyond just language proficiency. Therefore, this study explored the impacts of integrating AI-driven listening exams on foreign language learners’ mindsets, self-competence, resilience, and listening skills among Saudi Arabian EFL learners. To achieve this goal, 57 Saudi Arabian EFL learners were selected and divided into a control group (CG) and an experimental group (EG). The data on listening improvement, mindsets, self-competence, and resilience were collected using pretests and post-tests. The participants of both groups were trained in eight lessons of Tactics for Listening (Book 3) via the Duolingo application. The EG group then took AI-based exams by applying Nearpod, but the CG took traditional exams. After teaching all the lessons, the participants in both groups were given post-tests assessing their development in mindsets, self-competence, resilience, and listening skills. The findings revealed that participants exposed to AI-driven assessments showed significant enhancement in listening skills and reported improved self-competence, mindsets, and resilience. This study highlights the potential of AI to contribute holistically to language education, fostering technical skills and psychological and emotional development in EFL learners.